Research on national security risk assessment model of open government data - Biao WANG; Xingyang LIU; Ka XU; Wangyang LIU; Kenan WANG; Yuqing XIA (网络与信息安全学报)
As an important strategic resource of national and social development,the government open data is of great value.But China lack standards in the security risk assessment of government open data,especially the security of national data is at risk.Based on the theory of information security risk assessment,a government open data security risk assessment model was constructed with national security assets,open data vulnerability and security threat as the main security risk elements.Analytic hierarchy process (AHP) and fuzzy comprehensive evaluation methods were used to quantify and evaluate the security risks of government open data,and the validity of the model is verified by example.